PECULIARITIES OF THE DIGESTIVE SYSTEM DEVELOPMENT AND LIPID UPTAKE AMONG PREMATURE INFANTS - V.V. Dashichev; A.A. Andreev; N.V. Olendar' ("Paediatrician" Publishers LLC, 2006)
The article highlights the modern views on the nutritional support and energy supply for the premature neonates. In accordance with these viewpoints, the main source of energy is supposed to be lipids, which aside form all that, play the most important role in formation of biomembranes, cerebrum and organs of sight. In the meantime, premature neonates have poorly marked or virtually nonbexistent subcutaneous fat, which is called to be the main fat repository within the neonatal period, thus providing the body of a child with the required amount. Besides, the lipid uptake among premature infants is limited, resulting from the dismaturity of digestive apparatus. In this respect, breastfed children are in more favourable conditions. Women's milk is the only type of food, which is completely adjusted to «the limited capabilities» of the digestive functions of a neonate and meets all the needs of an infant as far as it relates to the food nutrients.Key words: lipids, premature neonate, infants, bile acids, aliphatic acids